Relocating middle powers: Australia and Canada in a changing world order - Cooper, Andrew Fenton 1950-; Higgott, Richard 1949-; Nossal, Kim R. 1952- (Canada and international relations, 1993)
The fall of the Berlin Wall and the disintegration of the Soviet Union were only two of the many events that profoundly altered the international political system in the late 1980s and early 1990s. In a world no longer dominated by Cold War tensions, nation states had to rethink their international roles and focus more on economic rather than military concerns. This book examines how two middle powers, Australia and Canada, engaged in the difficult process of relocating themselves in the rapidly changing international political economy. The authors argue that the concept of middle power has continuing relevance in contemporary international relations theory, and they present a number of case studies to illustrate the changing nature of middle power behaviour. In particular, they examine the trend towards the amalgamation of the foreign and trade ministries in both Canada and Australia, and the growing importance of regional trading blocs, particularly Asia-Pacific Economic Cooperation and the North American Free Trade Agreement. Australian and Canadian roles in the Gulf War are also scrutinized, showing how these middle powers found themselves caught up in the coalition-building dynamic that transformed Desert Shield into Desert Storm. Relocating Middle Powers is the first book to explore the similar ties and differences in the foreign policies of two middle powers in a new era of international relations. Focusing on the ability of middle powers to exercise technical and entrepreneurial leadership on a range of international issues, this book shows how and why middle powers will continue to be important international actors in the 1990s and beyond.